2005
DOI: 10.1038/sj.eye.6702014
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of retinal sensitivity measured with fundus-related microperimetry to visual acuity and retinal thickness in eyes with diabetic macular edema

Abstract: Aim To determine whether significant correlations exist between retinal sensitivity measured by fundus-related microperimetry and the visual acuity and the foveal thickness measured by optical coherence tomography (OCT) in eyes with diabetic macular edema (DME). Methods A retrospective chart review of 32 eyes with DME and 17 normal healthy eyes that had undergone fundus-related microperimetry and OCT. The macular sensitivity was measured using the recently introduced fundus-related microperimeter, Micro Perime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
73
0
5

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(84 citation statements)
references
References 11 publications
5
73
0
5
Order By: Relevance
“…9 Similar results were also reported by Vujosevic et al 10 We had concluded that the retinal sensitivity may be another measure that can be used to assess the effects of DMO. In both studies, the patients with DMO had not undergone any treatment for their macular oedema; however, in this study, the results of SMDLP on the VA and retinal sensitivity were different.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…9 Similar results were also reported by Vujosevic et al 10 We had concluded that the retinal sensitivity may be another measure that can be used to assess the effects of DMO. In both studies, the patients with DMO had not undergone any treatment for their macular oedema; however, in this study, the results of SMDLP on the VA and retinal sensitivity were different.…”
Section: Discussionsupporting
confidence: 76%
“…We have reported that the retinal sensitivity of the macular area determined by fundus-related microperimetry, MP1 (Nidek, Japan), was significantly correlated with the VA and foveal retinal thickness, and suggested that this may provide another method to assess the effects of DMO. 9 Similar findings were also reported, 10 and it was suggested that microperimetry may be of value in predicting the outcome of DMO. 10 The purpose of this study was to determine the retinal sensitivity of the macula area with the MP1 in patients with DMO treated with SMDLP, and to compare the retinal sensitivity with the best corrected visual acuity (BCVA) and the foveal thickness (FT) measured by optical coherence tomography (OCT).…”
Section: Introductionsupporting
confidence: 74%
“…Although there are reports evaluating central macular function in subjects with diabetic macular oedema using microperimetry with scanning laser ophthalmoscope, 23 fundus-related microperimeter 24 and multifocal ERG, 25 correlation of decreased retinal sensitivity as a corollary to reduced retinal thickness (in participants with no clinical diabetic retinopathy or maculopathy), as measured on spectral domain OCT and MP has not been reported earlier.…”
Section: Discussionmentioning
confidence: 99%
“…36 Significant correlations between mean retinal sensitivities measured by the MP-1, the foveal thickness in the OCT, and visual acuity were found in a retrospective chart review of patients with DME. 38 Vujosevic et al 36 compared the changes in macular sensitivity and macular thickness in different degrees of DME. They found macular sensitivity to be a relevant explanatory variable of visual function, independent of macular thickness data.…”
Section: Discussionmentioning
confidence: 99%